PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PERUSAHAAN INDEKS KOMPAS 100 - Suliastawan, I Wayan Edi; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p13, 2020)
The value of the company can provide maximum shareholder prosperity if the performance is good. one of them can be measured by profitability and other factors that influence company value are dividend policy. The purpose of this study was to determine the effect of profitability on firm value with dividend policy as a moderating variable in the Kompas 100 Index company. This research was conducted in all mining companies incorporated in the Kompas 100 Index on the Indonesia Stock Exchange (IDX). The number of samples, using the purposive sampling method is as many as 17 companies from 100 companies during the 2014-2018 period. The data analysis technique applied in this study is the regression analysis moderation. The results of the analysis produce, profitability has a significant positive effect on firm value. Dividend policy has a significant positive effect on firm value. Dividend policy moderates the effect of profitability on company value in the mining sector of the Kompas 100 Index. Keyword : profitability, dividend policy and company value .